Seismic design of bridges accounting for spatial variability of ground motion. - Lupoi, A. (Earthquake engineering & structural dynamics.)
The effects of the spatial variability of the ground motion on the response of bridge structures are investigated in this study. Following a well established convention, the phenomenon is represented as the combined effect of three causes : the loss of coherence of the motion with distance, the wave passage, and the local site conditions. Since the nature and amount of non-synchronism vary within ample limits a statistical approach is adopted. A parametric study is carried out on a representative set of bridges subjected to carefully selected combinations of the factors inducing spatial variability. The investigation has shown that the phenomenon affects the response considerably and, hence, the level of protection of these structures. It is observed that for all bridge types considered, the ductility demands at the base of the piers in the presence of spatial variability increase in the majority of cases. Further, for a given bridge type, the probabilities of failure vary by more than one order of magnitude depending on the combination of the parameters. Attention has been focused on a parameter representing the ratio between the maximum curvature ductility demand and the same quantity for the case of fully synchronous motion. This parameter has been used to correct the conventional synchronous design procedure by increasing the available ductility. The re-analysis of all the cases with a modified ductility capacity shows that the procedure is effective in reducing the fragilities to the values corresponding to synchronous input.